Exergetic performance analysis of high pressure air systems on ships - Karakurt, Asim Sinan; Ozsari, Ibrahim; Bashan, Veysi (INDERSCIENCE ENTERPRISES LTD, 2022)
Energy consumption, efficiencies, and eco-friendly issues are among the most researched topics. One of the high-energy consumption systems on ships is high-pressure air-start systems. This study performs energy and exergy analyses to optimise the use of high pressure air system with respect to performance outputs. The study calculates the exergy destructions resulting from the power consumed by the main compressors and the improper use of air stored at high pressures. Additionally, the ECOP is used to compare different models with respect to the First and Second Laws of Thermodynamics. The results from the analyses are as follows. The power consumptions are 1,530 kW, 1,283 kW, and 1,276 kW; the exergy destructions are 250 kW, 471 kW, and 450 kW; the ECOPs are 6.15, 2.72, and 2.84, respectively. The study presents the effects of sea water and ambient temperatures, and compressors' isentropic efficiencies on the power consumption, exergy destruction, and ECOP.
Keywords: ecological coefficient of performance; ECOP; air storage; exergy analysis; compressed air system; ENERGY-STORAGE; ECOLOGICAL COEFFICIENT; ECOP OPTIMIZATION; REFRIGERATOR; Thermodynamics; Energy & Fuels